Immunity Awareness—Strategies to Improve the Degree of Acceptance of Vaccines: A Systematic Review - Alejandro Martínez-Serrano; Montserrat Pulido-Fuentes; Blanca Notario-Pacheco; Ana María Palmar-Santos; Ana Isabel Cobo-Cuenca; Ana Díez-Fernández (Vaccines)
Background/Objectives: Vaccine hesitancy is one of the top ten threats to global health. It is necessary to develop appropriate strategies to address vaccine hesitancy. This systematic review aimed to analyze strategies used to improve the acceptance of vaccines, address doubts, and/or increase confidence and motivation in routine vaccination across all age groups. Methods: A systematic review was conducted of the MEDLINE, Dialnet, Scielo, CINAHL, and CENTRAL databases between 2018 and 2023. The inclusion criterion was full-text studies in English or Spanish that improve the degree of acceptance of vaccines and were evaluated by vaccination rate or pre- or postintervention tests. For data extraction, each study was categorized as community education, tailored messages, media, and new technologies. Results: A total of 1938 studies were identified, 38 of which were selected. New technology-based interventions used in the adult population for several vaccines offer broad reach, user interaction, and data accessibility. Tailored message strategies were used mainly among parents to foster strong relationships through respectful and empathetic dialog. Community education programs were targeted mainly at adolescents, emphasizing the use of structured, appropriate and interactive materials. Media campaigns were used as a support strategy for community education and new technology strategies due to their simplicity, wide coverage, and reach. Conclusions: The best strategies for reducing hesitancy are multicomponent interventions with structured and organized educational content based on the reasons for hesitancy and tailored to the target population. Therefore, caution must be taken when applying interventions, given that no single strategy can address this issue.